The Contributions of Nahdlatul Ulama to World Peace: A Taxonomy Literature Review - Hamid, Imron Rosyadi; Muhammad Iqbal Fajri , Aji Said (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
Entering a century after its establishment, it goes without saying that Nahdlatul Ulama (NU) has significantly contributed to World Peace through its engagements in societies, ranging from the promotion of moderate values to addressing conflicts in many countries. However, some empirical phenomena, especially when it was carried out by a faith-based entity, often get portrayed differently in academic settings. How do NU’s contributions to World Peace get incorporated into academic discourse? Using the taxonomy method, this article aims to analyze the contributions of NU to World Peace in the existing academic literature. It maps the consensus and ongoing debate on how NU exert its influence for peace and divides the literature into four taxonomical themes; (1) norm dissemination;(2) international diplomacy and peace-brokering; (3) education practices, and; (4) political practices. This paper concludes that NU’s contributions are widely recognized in academic discourse, but some gaps still need to be addressed in further research